Analisis Tantangan Manajemen Perubahan dalam Implementasi Sistem Informasi Pemerintah Daerah (SIPD) di BPKAD Kabupaten Dompu - Hairul Rohimin; Ega Saiful Subhan; Risca Ariska Ramadhan (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the implementation of the Regional Government Information System (SIPD) from a change management perspective at the Regional Financial and Asset Management Agency (BPKAD) of Dompu Regency. A qualitative research method with a descriptive approach was employed. Informants were selected purposively, specifically comprising employees who directly operate the SIPD. Data collection involved interviews, observation, and documentation, while data analysis utilized data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of SIPD supports change management at BPKAD Dompu Regency through alignment with national policies, adequate technological readiness, effective communication and coordination among employees, and positive competition that fosters improvements in employee competence and performance. Thus, the implementation of SIPD supports the organizational change process and enhances the effectiveness of regional financial management at BPKAD Dompu Regency.